Re-Layout Tata Letak Bagian Percetakan Menggunakan Calullar Manufacturing System - Yohanes Anton Nugroho (Jurnal Penelitian Rumpun Ilmu Teknik, 2022)
Material handling in the production division of publisher X encountered several obstacles, including the transfer of material between production processes having cross-movement flows. This condition occurs as a result of an irregular engine layout. The impact of the conditions in the transfer of material in the production process is the distance of the transfer to be 968.6 m/day. This condition causes some machines to be repositioned, so that material transfer can run faster and more efficiently. One of the efforts to reduce material transfer is to re-plan the placement of production facilities by adopting the concept of a cellular manufacturing system or cellular manufacturing system that is feasible to be applied to the production process of publisher X. The cellular manufacturing system was chosen because it is in accordance with the number of characteristics of the publishing industry that requires the ability to anticipate changes. This rapid demand suits a particular market. This article describes how the results of rearranging and minimizing the distance of moving raw materials in the production section of publisher X by adopting the concept of a cellular manufacturing system and rearranging the layout of production facilities by using sorting using Sorting Algorithms. The selection of the Sorting Algorithms is based on consideration of the order of the output which is not coherent, so it needs to be sorted. Efficient sorting is needed to determine the part-machine incidence matrix which is then used in the development of cellular manufacturing systems. Program development on Visual Studio 2012 software shows the results of facility layout planning by grouping 20 machines and 11 products with this layout change, the total material handling distance is reduced by 371.8 m or by 61.61%